Higher prevalence of QTc interval prolongation among virologically suppressed older people with HIV. (1st December 2022) - Theerasuwipakorn, Nonthikorn; Rungpradubvong, Voravut; Chattranukulchai, Pairoj; Siwamogsatham, Sarawut; Satitthummanid, Sudarat; Apornpong, Tanakorn; Ohata, Pirapon J.; Han, Win Min; Kerr, Stephen J.; Boonyaratavej, Smonporn; Avihingsanon, Anchalee
Abstract : Objective: To assess the prevalence, and factors associated with QTc interval prolongation, among 383 virologically suppressed people with HIV (PWH), without evidence of cardiovascular disease and active opportunistic infections in Thailand. Design: Cross-sectional study. Methods: Resting 12-lead digital ECGs were performed in 2019. QT interval corrected for heart rate (QTc) >450 ms in males and >460 ms in females was defined as QTc interval prolongation. We used multivariable logistic regression to investigate factors associated with QTc interval prolongation. Results: Mean (standard deviation) age was 56 (5.5) years and 42% were female. The median current CD4+ was 619 (interquartile range [IQR] 487, 769) cells/mm 3 . The median duration of antiretroviral therapy (ART) was 11.9 (IQR 7.1–16.1) years. Commonly used ART were rilpivirine (37.9%), efavirenz (20.1%), atazanavir/ritonavir (15.7%), lopinavir/ritonavir (12.3%) and dolutegravir (5%). The prevalence of QTc interval prolongation was 22.7%. In multivariable analysis, older age (odds ratio [OR] 1.07, 95% confidence interval [CI] 1.02–1.12, P = 0.005), female sex (OR 1.69, 95% CI 1.01–2.82, P = 0.046) and increasing BMI (OR 1.08, 95% CI 1.01–1.15, P = 0.03) were associated with QTc interval prolongation. With every 1-year increase in age, the odds of QTc interval prolongation increased by 7%. Conclusions: In this well-suppressed aging Asian HIV cohort, the prevalence of QTc interval prolongation was relatively high, and associated with increasing age, female sex, and higher BMI. For PLWH with these characteristics, QTc interval should be monitored before and after initiating any medications known to prolong QTc intervals, to prevent fatal cardiac arrhythmias.